Sumber Nilai-Nilai dalam Manajemen Pendidikan Islam - Jamilah Vikamila; Poppy Rachman; Indirwan (At- Ta'lim : Jurnal Pendidikan, 2021)
This paper presents a discussion about the source of the values of Education management where the source of value in question is tawhid, by using the method of file research aim at revealing source values and values contained in the management of Islamic education, where the results show that human beings have the fitrah to believe in relying on all things only to god and man just to do the scenario that has been made by Allah swt , By holding on to the Qur'an and hadith. Therefore, born as a source of value management of Islamic education, this concept is related to self-management (personal) but can be applied in the context of social charity including in the management of Islamic education. If we associate this with the Islamic education management system, then the intention is the same as Pleaning, An-Nashabu in identical with the organization and actuating while Muhasabah, Tasyakkur, and Tawakkal are contained as controlling in Islamic education management